General View of the Character of the Administrative Dispute in the First Yugoslav State - Bačanin, Vojislav (Serbian political thought, 2023)
The text is an attempt to re-test certain authorial hypotheses regarding the character of the administrative dispute in the first Yugoslav state. In the first part of the paper, the readers are briefly reminded of the basic theoretical assumptions concerning the concept, subject and classification of administrative dispute. The second part of the paper presents a review of the normative framework and accepted legal solutions in the analyzed period. In the third part of the paper, the author addresses the more significant doctrinal dilemmas on this issue. In the last part, instead of concluding, a simplified assessment of the character and legal nature of the administrative dispute in the mentioned period is offered. It is concluded that the system of administrative court control of the administration belonged to the group of European-continental ones, that the subject of the administrative dispute was determined by a combination of the general clause method and the negative enumeration method, and the dispute was defined as a subjective dispute about the legality of the administrative act. A particular emphasis is placed on the existence of an objective administrative dispute and the views on the existence of a form of full jurisdiction in the law of the first Yugoslav state are accepted.
Keywords: administrative judiciary; administrative dispute; administrative court; State Council; subjective dispute; objective dispute; dispute of full jurisdiction